Ciprofloxacin versus colistin prophylaxis during neutropenia in acute myeloid leukemia: two parallel patient cohorts treated in a single center - Michele Pohlen; Julia Marx; Alexander Mellmann; Karsten Becker; Rolf M. Mesters; Jan-Henrik Mikesch; Christoph Schliemann; Georg Lenz; Carsten Müller-Tidow; Thomas Büchner; Utz Krug; Matthias Stelljes; et al. (Haematologica, 2016)
Patients undergoing intensive chemotherapy for acute myeloid leukemia are at high risk for bacterial infections during therapy-related neutropenia. However, the use of specific antibiotic regimens for prophylaxis in afebrile neutropenic acute myeloid leukemia patients is controversial. We report a retrospective evaluation of 172 acute myeloid leukemia patients who received 322 courses of myelosuppressive chemotherapy and had an expected duration of neutropenia of more than seven days. The patients were allocated to antibiotic prophylaxis groups and treated with colistin or ciprofloxacin through 2 different hematologic services at our hospital, as available. The infection rate was reduced from 88.6% to 74.2% through antibiotic prophylaxis (vs. without prophylaxis; P=0.04). A comparison of both antibiotic drugs revealed a trend towards fewer infections associated with ciprofloxacin prophylaxis (69.2% vs. 79.5% in the colistin group; P=0.07), as determined by univariate analysis. This result was confirmed through multivariate analysis (OR: 0.475, 95%CI: 0.236–0.958; P=0.041). The prophylactic agents did not differ with regard to the microbiological findings (P=0.6, not significant). Of note, the use of ciprofloxacin was significantly associated with an increased rate of infections with pathogens that are resistant to the antibiotic used for prophylaxis (79.5% vs. 9.5% in the colistin group; P